2006
DOI: 10.1080/02713680500536746
|View full text |Cite
|
Sign up to set email alerts
|

Type III Secretion System–Associated Toxins, Proteases, Serotypes, and Antibiotic Resistance ofPseudomonas aeruginosaIsolates Associated with Keratitis

Abstract: The association between possession of toxin gene-related type III secretory system, protease profiles, O serotypes, and antibiotic resistance patterns was characterized genetically and phenotypically in 46 keratitis isolates of Pseudomonas aeruginosa. There was no significant difference in exoU or exoS prevalence among the keratitis strains. Distinct protease profiles were seen in isolates harboring either exoU or exoS genes. One hundred percent (13/13) of serotype E (O:11) strains contained type III secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 48 publications
4
42
1
Order By: Relevance
“…Since the introduction of second-generation fluoroquinolones ciprofloxacin and ofloxacin in the 1990s, the reported incidence of in vitro resistance to these antibiotics among bacteria isolated from bacterial keratitis and endophthalmitis has been steadily increased in the USA (Hwang, 2004) and India (Smitha et al, 2005). In the current study, 11% of all keratitis isolates in Australia were non-susceptible to ofloxacin, which is higher than the results of previous report (Zhu et al, 2006) in which the strains used were isolated through the years 1986 to 2004. An increasing trend of fluoroquinolone resistance was found in noncontact lens-related isolates, as the resistance rate increased from 8% (2/24) before year 2005 to 24% (4/17) from year 2006 (Choy et al, 2008).…”
Section: Discussioncontrasting
confidence: 54%
“…Since the introduction of second-generation fluoroquinolones ciprofloxacin and ofloxacin in the 1990s, the reported incidence of in vitro resistance to these antibiotics among bacteria isolated from bacterial keratitis and endophthalmitis has been steadily increased in the USA (Hwang, 2004) and India (Smitha et al, 2005). In the current study, 11% of all keratitis isolates in Australia were non-susceptible to ofloxacin, which is higher than the results of previous report (Zhu et al, 2006) in which the strains used were isolated through the years 1986 to 2004. An increasing trend of fluoroquinolone resistance was found in noncontact lens-related isolates, as the resistance rate increased from 8% (2/24) before year 2005 to 24% (4/17) from year 2006 (Choy et al, 2008).…”
Section: Discussioncontrasting
confidence: 54%
“…Other research suggested that the multidrug resistance in ocular P. aeruginosa was more commonly associated with strains having cytotoxicity and exoU gene, and belonging to serotype E (Zhu et al 2006). Recently, Zaborina et al (2006) screened consecutively isolated MDR P. aeruginosa clinical strains for their ability to disrupt the integrity of human cultured intestinal epithelial cells (Caco-2) and correlated these findings to related virulence phenotypes such as adhesiveness, motility, biofilm formation and cytotoxicity.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have linked multidrug resistance in P. aeruginosa to TTSS phenotypes in ocular, blood, urine, and wound isolates (26, 27). Wong-Beringer and colleagues (27) studied this association by concentrating on fluoroquinolone-resistant clinical isolates of P. aeruginosa .…”
Section: Discussionmentioning
confidence: 99%